The Effect of Bupivacaine on the Efficacy of Antibiotic Coating on Penile Implants in Preventing Infection. Issue 3 (18th July 2019) - Lokeshwar, Soum D.; Horodyski, Laura; Lahorewala, Sarrah S.; Morera, Daley S.; Arora, Himanshu; Kava, Bruce; Ramasamy, Ranjith
Abstract: Background: In an effort to reduce dependence on opioids following inflatable penile prosthesis placement, intra-operative soaking of the implant in Bupivacaine (BUP) has been proposed as part of a multimodal approach to pain control. However, no study has shown if the addition of BUP affects the antimicrobial properties of InhibiZone on AMS700 (Boston Scientific, Marlborough, MA) and/or of antibiotic soaked Titan Coloplast (Coloplast Corporation, Minneapolis, MN). Aim: To determine if BUP alters the zone of inhibition (ZOI) against Staphylococcus epidermidis ( S epidermidis ) and Escherichia coli ( E coli ), common gram-positive and gram-negative bacterial causes of infection, respectively, created by InhibiZone coated AMS and/or by antibiotic-soaked Coloplast implant. Methods: S epidermidis and E coli were spread on agar plates. After a 30-minute incubation, four AMS with InhibiZone strips treated with sterile saline or BUP (1.25 mg/mL) were placed on a plate. 4 Coloplast strips were dipped in varying routinely used concentrations of Rifampin (0–10 mg/mL) plus Gentamicin (0–1 mg/mL; rifampin and gentamicin (R+G)) solution with or without BUP. The ZOI for AMS with InhibiZone and Coloplast dipped in antibiotic solution was measured using ImageJ software. Normalized ZOI was calculated as (ZOI area/plate area) × 100. Unpaired t -test compared the mean ± SD ZOI between BUP and no BUP groups (n = 4/group). Outcomes: The primary outcome of the study was the ZOI against E coli and S epidermidis at 24 and 48 hours. Results: Growth of both S epidermidis and E coli at 24 and 48 hours of incubation was inhibited in both implants and the addition of BUP did not alter the ZOI. Coloplast strips dipped in R+G produced a ZOI in a dose-dependent manner. Interestingly, the ZOI against S epidermidis compared to that of E coli was much wider for both implants. Clinical Implications: This suggests that the use of BUP does not affect the protective effects of antibiotic dips and can potentially be used during penile prosthesis surgery pending clinical trials. Strengths and Limitations: This is the first study to evaluate the effect of BUP on anti-bacterial dips. As with all in vitro analysis, further research must be done to see if these findings hold true in the clinical setting. Conclusions: The addition of BUP does not impede the in vitro antibacterial activity of InhibiZone-coated AMS or R+G-soaked Coloplast. Whether these in vitro findings translate to surgical outcomes needs to be evaluated in future preclinical trials.